Curves that heal and inspire - Ahmad, Afida; Samsudin, Syafiza Saila; Mohd Najib, Norliana (Universiti Teknologi MARA, Kedah, 2025)
Curves are fundamental elements in both nature and design, representing smooth, continuous lines that can vary in complexity and form. They are essential in various fields, from the graceful arcs seen in architecture to the intricate paths in computer graphics. In the realm of computer graphics and animation, one of the most powerful tools for creating smooth and intricate shapes is the Bézier curve. A Bézier curve is a smooth, mathematically defined curve constructed using a set of points known as control points. These control points may not necessarily lie directly on the curve, but they significantly influence its shape and trajectory.